2021
DOI: 10.1371/journal.pcbi.1008942
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of metabolic pathway dependencies in cancer cell lines

Abstract: The metabolic reprogramming of cancer cells creates metabolic vulnerabilities that can be therapeutically targeted. However, our understanding of metabolic dependencies and the pathway crosstalk that creates these vulnerabilities in cancer cells remains incomplete. Here, by integrating gene expression data with genetic loss-of-function and pharmacological screening data from hundreds of cancer cell lines, we identified metabolic vulnerabilities at the level of pathways rather than individual genes. This approa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Over recent months, more than 1300 metabolic reactions and 120 metabolic enzymes have been integrated into the human causal interactome. The enzymatic reactions have been organized into nine pathways, concentrating on pathways whose activities are deregulated in cancer cells (glycolysis and gluconeogenesis, citric acid cycle, glycogenesis, glycogenolysis, aspartate and asparagine metabolism, fatty acid synthesis, glutamine metabolism, nucleotide biosynthesis, pentose phosphate ( Joly, Chew, and Graham 2021 ). In addition, we have identified, in each pathway, key enzymes whose activities are rate limiting and are therefore more likely to affect the metabolic flux when their concentrations or activities are modulated ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over recent months, more than 1300 metabolic reactions and 120 metabolic enzymes have been integrated into the human causal interactome. The enzymatic reactions have been organized into nine pathways, concentrating on pathways whose activities are deregulated in cancer cells (glycolysis and gluconeogenesis, citric acid cycle, glycogenesis, glycogenolysis, aspartate and asparagine metabolism, fatty acid synthesis, glutamine metabolism, nucleotide biosynthesis, pentose phosphate ( Joly, Chew, and Graham 2021 ). In addition, we have identified, in each pathway, key enzymes whose activities are rate limiting and are therefore more likely to affect the metabolic flux when their concentrations or activities are modulated ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Plasma metabolomic profiling provides a snapshot of metabolic changes [ 35 ], which are a good choice for the investigation on diseases and responses to treatment [ 36 ]. We identified 3 metabolic pathways that were significantly altered by HDMTX.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the previous KEGG pathway enrichment analyses, the present observations indicated that GDY-Cu mainly caused intracellular fatty acid and lipid metabolism in cancer cells. Metabolic reprogramming is a complex biological process in which various metabolic pathways interact with each other [55]. Aerobic glycolysis plays a vital role in the development of PCa.…”
Section: Untargeted Metabolomics Analysis Reveals Alterations In Du14...mentioning
confidence: 99%